Invadopodia, Regulation, and Assembly in Cancer Cell Invasion - Saykali, Bechara A. (2014)
The occurrence of invadopodia has been, since its characterization, a hallmark of cancerous cell invasion and metastasis. These structures are now the subject of a controversy concerning their cellular function, molecular regulation, and assembly. The terms invadopodia and podosomes have been used interchangeably since their discovery back in 1980. Since then, these phenotypes are now more established and accepted by the scientific community as vital structures for 3D cancer cell motility. Many characteristics relating to invadopodia and podosomes have been elucidated, which might prove these structures as good targets for metastasis treatment. In this review, we briefly review the actin reorganization process needed in most types of cancer cell motility. We also review the important characteristics of invadopodia, including molecular components, assembly, markers, and the signaling pathways, providing a comprehensive model for invadopodia regulation.